2014
DOI: 10.2478/johh-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and comparison of stream power in-channel and on the floodplain in a German lowland area

Abstract: Extensive lowland floodplains cover substantial parts of the glacially formed landscape of Northern Germany. Stream power is recognized as a force of formation and development of the river morphology and an interaction system between channel and floodplain. In order to understand the effects of the river power and flood power, HEC-RAS models were set up for ten river sections in the Upper Stör catchment, based on a 1 m digital elevation model and field data, sampled during a moderate water level period (Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Later in the rainy season (Fig. 8), the sediment concentrations decrease because the rill formation and expansion decline (Tebebu et al, 2010;Tilahun et al, 2013a;Tilahun et al, 2013b;Zegeye et al, 2010) with greater concentrations during high flow events compared to the small storms due to less stream power (Song et al, 2014). Though concentrations decrease due to the vegetation cover, unlike in developed countries, the cover does not provide full canopy because of the low nutrient status of the soils and lower fertilizer application in the Debre Mawi watershed.…”
Section: Suspended Sediment Loads and Concentrationsmentioning
confidence: 99%
“…Later in the rainy season (Fig. 8), the sediment concentrations decrease because the rill formation and expansion decline (Tebebu et al, 2010;Tilahun et al, 2013a;Tilahun et al, 2013b;Zegeye et al, 2010) with greater concentrations during high flow events compared to the small storms due to less stream power (Song et al, 2014). Though concentrations decrease due to the vegetation cover, unlike in developed countries, the cover does not provide full canopy because of the low nutrient status of the soils and lower fertilizer application in the Debre Mawi watershed.…”
Section: Suspended Sediment Loads and Concentrationsmentioning
confidence: 99%
“…4). Calculations of unit stream power using HEC-RAS (see for example, Song et al, 2014) by Professor Hugo Loaiciga, member of our research team (Loaiciga, personal written communication, 2008), and the author concluded that Unit stream power in 2005 against the bluff at Monte Vista across from the levee at Live Oak Acres was about 800 W/m 2 --sufficient using Costa (1983) to move boulders up to about 1000 mm in diameter. By comparison, the unit stream power just upstream of the levee against the eastern bank of the river was about 115 W/m 2 ) --sufficient to move particles of about 200 mm diameter (Costa, 1983).…”
mentioning
confidence: 98%
“…For the drainage network ordering process, we estimated a length of 100 m based on field survey observations. The final catchment extraction and merge operations were performed using pre-defined outflow points, based on the water course distribution, easily accessible and suitable to measure with flow meters (Song et al, 2014).…”
Section: Data Processingmentioning
confidence: 99%
“…Song et al (2014) described this as the first step before analyzing the alluvial and hydrological effects of river and estuarine systems. In the absence of a sub-basin discharge monitoring, it becomes more efficient and realistic to estimate the basin hydrological parameters if the spatial distribution is consistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation